P-83 A breath of fresh air. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Groves, Karen; Webster, Laura; Jones, Timothy
Abstract : Background: Breathlessness is common in advanced disease. Those with cancer often have good support, compared with end stage non-malignant disease. A multiprofessional short specialist palliative intervention (SSPI) includes symptom management, coping and advance care planning. A visual analogue scale (VAS) pre and post intervention addresses four specific areas: breathlessness, anxiety, sleep quality and energy levels. Opioids for breathlessness now given as slow release morphine (max 30 mg/24 hrs) rather than immediate release. Aims: To assess appropriateness of referrals, subjective symptom improvement and advance care planning conversations offered. Methodology: Retrospective audit 18 months' referrals, for VAS score pairs, subjective assessment of symptoms, GSF registration, ACP discussions, PPC recording and achievement (if died). Results: 52 patients identified – 16 excluded, 14 cancer, 1 DNA, 1 moved away. 36 records reviewed. 90% pulmonary disease, 5% cardiac, 5% MND. VAS score pair recorded 65% – breathlessness reduced 57%, worsened 17%; anxiety reduced 70%, worsened 8%; sleep quality improved 35%, unchanged 65%; energy levels improved 40%, worsened 8%. PPC recorded 94% – home 72%, not home 28%. 44% clinic attenders died, 81% achieved PPC and 62% supported by individualised plan for care. 100% discussed wishes and preferences, ACP discussed 72%, formal ACP by a few, ADRT 8%. DNACPR in place for 15%. Conclusions: Initial poor VAS completion addressed by one doctor being responsible for SSPI. Referral rates increased and inappropriate referrals declined. Multiprofessional approach appears to help patients and carers manage/cope better with daily symptoms. Two patients showed dramatic improvement in breathlessness, anxiety and energy on a second intervention attendance. VAS scale improvements appear more marked with modified release morphine compared to immediate release (audit ongoing). Clinic appears to be encouraging patients to engage in process of advance care planning.